Empowering the Java Sindoro-Sumbing Geographical Indication Community through Legal Assistance for Intellectual Property Protection - Waspiah Waspiah; Ridwan Arifin; Dian Latifiani; Umi Afiatun; Ana Sofía Gabriela (Faculty of Law, Universitas Negeri Semarang, 2026)
This study examines the role of legal assistance in empowering the Masyarakat Perlindungan Indikasi Geografis (MPIG) Java Sindoro-Sumbing community in Temanggung, Indonesia, to protect their communal intellectual property. Focusing on the unique geographical indication (GI) of coffee from the Sindoro-Sumbing region, the research addresses the critical challenges faced by local communities in safeguarding their heritage against potential misuse and unauthorized commercialization. Historically, such communities have lacked the legal expertise and resources to navigate the complexities of intellectual property law, leaving their valuable assets vulnerable. Our research employs a qualitative, case-study approach, documenting the process of providing targeted legal support to the MPIG. This assistance included educating community members on GI rights, assisting with the legal registration process, and preparing them to handle potential disputes. We analyze the outcomes of this intervention, highlighting how legal empowerment has not only strengthened the community's capacity to defend its GI but has also fostered a greater sense of ownership and collective identity. The findings suggest that proactive legal assistance is a vital tool for community-based organizations seeking to protect their intangible cultural and economic assets. By bridging the gap between legal frameworks and grassroots needs, this approach offers a sustainable model for communal resource management. The study concludes that for regions rich in unique geographical products, legal support is not merely a reactive measure but a proactive strategy for ensuring economic justice and cultural preservation.